Aerodynamic studies on multi-storied building / Saw Cheng Lee, M. Govardhan and Mohammed Kamel Wan Ibrahim - Saw, Cheng Lee; Govardhan, M.; Wan Ibrahim, Mohammed Kamel (2006)
Wind tunnel tests on structural models are needed when the full-scale structures cannot be tested or analysed. Very few industrial structures can be analysed accurately, particularly when they have solid and not lattice faces. Objects of tunnel tests include bridges, chimneys, vehicles, buildings, and radars. The model under investigation is non aerodynamic building model. The wind tunnels tests on the building model are carried out to include flow visualization, pressure and velocities distributions on the various faces of the building. Flow visualization tests are carried out by using the woollen tuft technique at three different speeds, i.e., 22 ms-1, 30 ms-1 and 38 ms-1. In addition, for each speed, the building's yaw angle was varied from -15° to +15°. Flow visualization by wool tuft technique is able to show the characteristic of the flow around the building. Pressure distribution tests on the building model are carried out by using the wind tunnel technique and Bernoulli Principle. Around 164 static pressure ports available on all faces of the building are connected to a water tube manometer. Results showed high pressure along the centre line of the front surface of the building. CFD analyses of the flow are carried out by using Cosmosflowork 2004. The computational results are compared with the experimental results.